Africa: an emerging markets frontier. (1st January 2012) - Vadra, Ratna
Africa is in competition for international capital and resources and is currently ranked in the same category as Latin America and Eastern Europe in terms of attractiveness for investors. There has been a fundamental shift in the global economy over the past few years, with emerging markets not only dominating investor attention and capital flows, but also playing an increasingly strategic role in defining the global economic agenda. African markets must position themselves appropriately in this shifting landscape to accelerate growth and development and avoid getting left behind by other emerging markets and regions. The current article highlights the shift of Investment scenario from developing to undeveloped countries with special reference to Africa. The rise of India and China in Africa is seen in the current years. The purpose of this paper is to find point the reasons of the foreign direct investment (FDI) in Africa. Africa's FDI inflows are highly increasing, it, is suggested that countries and companies that's its high time, one should invest in Africa as there is huge potential for natural resources.